2021
DOI: 10.51620/0869-2084-2021-66-3-139-146
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of soluble forms of immune checkpoint PD-1/PDL1 receptor and ligand in blood plasma of gastric cancer patients

Abstract: Analysis of long-term treatment results of 101 primary gastric cancer patients at various stages of the tumor process followed during 1 - 41 months (median - 6,4 months) from the onset of specific treatment are presented depending on the levels of soluble forms (s) of PD-1 receptor and its ligand PD-L1 in blood plasma. Overall survival assessed by Kaplan-Meyer analysis and with the help of Cox multiparametric regression model was applied as the criterion of prognostic value. It was found that at high (≥ 35 pg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In most cases, the level of circulating sPD-L1 was found to be enhanced in the plasma of patients with the indicated pathology compared to healthy control (see Table 1 . For the oncology indications, the presence of sPD-L1 and its significance are discussed in the following studies: AEC [ 41 ]; BTC [ 42 , 43 ]; brain tumors [ 26 , 44 ]; CRCC [ 45 , 46 ]; CRC [ 47 ]; cutaneous melanoma [ 48 ]; DLBCL [ 49 , 50 ]; EOC [ 51 , 52 ]; ENKTL [ 53 , 54 ]; HNSCC [ 36 ]; HCC [ 55 , 56 , 57 ]; HL [ 54 , 58 ]; mesothelioma [ 59 , 60 ]; NC [ 61 , 62 ]; PGC [ 63 , 64 , 65 ]; NSCLC [ 66 , 67 ]; PC [ 68 ]; PCNSL [ 50 ]; STS [ 69 , 70 ]; TC [ 71 ]; TNBC [ 72 ]; WM [ 73 ].…”
Section: The Pd-1/pd-l1 Checkpointmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, the level of circulating sPD-L1 was found to be enhanced in the plasma of patients with the indicated pathology compared to healthy control (see Table 1 . For the oncology indications, the presence of sPD-L1 and its significance are discussed in the following studies: AEC [ 41 ]; BTC [ 42 , 43 ]; brain tumors [ 26 , 44 ]; CRCC [ 45 , 46 ]; CRC [ 47 ]; cutaneous melanoma [ 48 ]; DLBCL [ 49 , 50 ]; EOC [ 51 , 52 ]; ENKTL [ 53 , 54 ]; HNSCC [ 36 ]; HCC [ 55 , 56 , 57 ]; HL [ 54 , 58 ]; mesothelioma [ 59 , 60 ]; NC [ 61 , 62 ]; PGC [ 63 , 64 , 65 ]; NSCLC [ 66 , 67 ]; PC [ 68 ]; PCNSL [ 50 ]; STS [ 69 , 70 ]; TC [ 71 ]; TNBC [ 72 ]; WM [ 73 ].…”
Section: The Pd-1/pd-l1 Checkpointmentioning
confidence: 99%
“…At the same time, a high level of soluble PD-L1 in peripheral blood often predicts poor prognosis in patients with solid tumors [ 111 ]. However, as an isolated marker, it cannot be considered a predictor of overall survival of patients with solid tumors [ 63 ]. The level of sPD-L1 does not always correlate with response to immune-sensitivity, notably in lung cancers [ 45 , 66 ].…”
Section: Significance Of Soluble Pd-l1 In Cancermentioning
confidence: 99%
“…These co-inhibitory ICPs are expressed on various cell types in the tumor microenvironment (TME), including immune suppressor cells of the adaptive and innate immune systems, as well as tumor cells per se and cancer-associated fibroblasts, among others [12] , [13] , [14] . In addition, co-inhibitory soluble ICPs (sICPs) have also been detected in the systemic circulation of cancer patients with various types of advanced malignancies, including, but not limited to, melanoma and cancers of the breast, esophagus, head and neck, lung and stomach [15] , [16] , [17] , [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a series of papers, different authors recently suggested a role of sPD-L1 as a biomarker in very different cancer entities and have suggested a diagnostic, prognostic and predictive role of this molecular marker in cancers originating from the urothelium, lung and brain [ 12 , 13 , 14 ]. In addition, sPD-L1 was found to be a prognostic marker in gastrointestinal stromal cancers and gastric cancers [ 15 , 16 ]. Therefore, evaluation of PD-L1 expression and/or PD-L1 serum levels as a surrogate for PD-L1 expression has been proposed as a valuable tool for the estimation of patients’ prognosis in manifold cancers.…”
Section: Introductionmentioning
confidence: 99%